Creating Human Value as Public Management Theory - Drew, Joseph (Routledge, 2025)
Creating Human Value (CHV) is a powerful public management theory that places the person at the centre of all decision-making. It is founded on millennia-old natural law philosophy, updated to cope with contemporary problems. At the heart of CHV is the ideal of human flourishing - this is achieved through pursuing the common good, via public policy, in a way that respects human dignity. To paraphrase Socrates, it is about caring for the city, rather than merely the city's possessions.This book is the product of almost a decade of research and teaching of this compelling alternate public management theory to government decision-makers in Australia and abroad. In sum, CHV is a much-needed antidote to currently popular public management approaches that have unduly prioritized the common good over dignity with catastrophic consequences for the lives of many people.This book will appeal to readers interested in public management, public policy, and government.
Keywords: Public administration.; Creating Human Value; Creating Public Value; Natural law philosophy; Principle of double effect; Principle of subsidiarity; Public management; Public governance; Government; Proportionate equity; Virtue; Public administration; elektronické knihy; electronic books